Kualitas dan Kepuasan Pengguna Terhadap Sistem Informasi Akademik Berbasis Web - Suaryana, I Gusti Ngurah Agung; Damayanthi, Eka; Merkusiwati, Lely (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 11 No 2 (2016), 2017)
The purpose of this study is to evaluate the quality of web-based academic information system in FEB Unud and its impacts to users’ satisfaction. The users of this system are students, lectures, and academic staffs of FEB Unud. This study surveys the perception of students, lectures, and staffs and their satisfaction on the quality of the Academic Information System. The quality system includes three elements, namely the information quality, the system quality, and the service quality. The quality of this web-based academic information system is expected to affect the satisfaction of the users. For FEB Unud, the result of this study is expected to give the feedback for the faculty leaders in order to take further corrective measures. For other educational institutions, the study is expected to be a model of academic information system development.
Keywords: system information quality, user satisfaction, academic information systems, information quality, system quality, service quality